-2x(5x-8)=6x

Simple and best practice solution for -2x(5x-8)=6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x(5x-8)=6x equation:


Simplifying
-2x(5x + -8) = 6x

Reorder the terms:
-2x(-8 + 5x) = 6x
(-8 * -2x + 5x * -2x) = 6x
(16x + -10x2) = 6x

Solving
16x + -10x2 = 6x

Solving for variable 'x'.

Reorder the terms:
16x + -6x + -10x2 = 6x + -6x

Combine like terms: 16x + -6x = 10x
10x + -10x2 = 6x + -6x

Combine like terms: 6x + -6x = 0
10x + -10x2 = 0

Factor out the Greatest Common Factor (GCF), '10x'.
10x(1 + -1x) = 0

Ignore the factor 10.

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1

Solution

x = {0, 1}

See similar equations:

| 8a+3=3 | | 9x-1=125 | | 1/8(5x+4)=3.4 | | (1)/(8)x=(1)/(2) | | (x-5)/(3*x)+(6/2*x+1)=0 | | (8x+9)(7x^2+9x+9)= | | (5)/(6)x=-15 | | 5t-t-7=3t-4 | | 3/4(-4y-8x+4z) | | 6(2q+1)=9q-12 | | (7x^2-8x-10)(x-9)= | | 5x=4x-3/4 | | 3/5*10x | | 8.4o-6.8=14.3+6.3o | | 5+4y=2y-13 | | 10m+16n=140 | | -2x^4y^2= | | -27x-9y=18 | | N^2+5n-266=0 | | 2(3x-2)-5x=5-2x | | X-(45)=16 | | (-2x^4y^2)= | | 73-5x=40x+23 | | 0=x^5+4x^4+4x^3 | | (n-5)*8=16 | | N^2+5n-265=0 | | 2x+8=8x-5 | | 6x^2+7x+3=26 | | x-3y=19 | | 36/9*2+6 | | 3t-7=-2t+38 | | y^2+4y^1+2y^0=0 |

Equations solver categories